Attitudes of secondary school students towards physical education lessons - Gądek, Adrian; Madejski, Eligiusz (Health Promotion & Physical Activity, 2025)
Introduction: Shaping students’ attitudes towards effort, health, physical education lessons, and physical activity has become one of the main goals of physical education. Emotions play a crucial role in the educational process, as they influence student engagement and the long-term shaping of attitudes. Students’ attitudes towards broadly understood physical culture impact their later behaviors related to health, regardless of the influence of school or family. Material and methods: The study employed a diagnostic survey method using the Baumgartner and Jackson Attitude Questionnaire to measure attitudes in three dimensions: evaluation, intensity, and activity. The survey was conducted among 751 students from different secondary schools (59.4%), technical schools (32.5%), and vocational schools (8.1%) in Tarnów. The results were processed using various descriptive statistics and inferential techniques, with the significance level set at α = 0.05. Results: The overall opinions of students regarding their attitude towards physical education lessons can be considered optimistic (23.63 ± 3.69). Women (23.98 ± 3.20) showed slightly higher scores than men (23.28 ± 4.09), and the differences were statistically significant at the α < 0.05 level. Men, on the other hand, attributed statistically significantly greater importance to the intensity (15.42 ± 4.39) and activity (12.74 ± 4.89) dimensions during lessons, which may have contributed to their stronger stimulation. The analysis of the results indicated that physical education lessons had a less positive value for students from general secondary schools (23.34 ± 3.57) compared to their peers from technical schools (23.89 ± 3.77). However, in both groups, positive attitudes prevailed. Practical implication: When planning physical education lessons, it is worth considering all components and dimensions of attitudes towards physical culture, including physical education lessons. A holistic approach to the topic of shaping attitudes will allow for a stronger influence on the changes in this area of activity.